Psychometric Properties of the Standardised Instruments that are Used to Measure (Pragmatic) Intervention Effects in Autistic Children: A Systematic Review - Tatiana Pereira; Ana Cláudia Lopes; Ana Margarida Ramalho; Marisa Lousada (Autism and Developmental Language Impairments)
Background and aims Pragmatic language difficulties can negatively influence the learning, socialization, and mental health of children diagnosed with autism spectrum disorder (ASD). Several studies have sought to determine the effects of interventions, including competencies to help these children use language for social purposes. However, are the instruments used to measure the results of the interventions appropriate and psychometrically adequate? This systematic review aims to analyze the psychometric properties of the standardized instruments that are used to measure the effects of interventions addressing (not exclusively, but also) pragmatic language competencies for autistic children. Method Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, systematic literature research was carried out in four electronic indexing databases: CENTRAL, PubMed, Web of Science, and Scopus. Results A total of 49 studies from 2005 to 2023 were included and 19 standardized instruments were identified. Conclusions After analyzing the instruments psychometric properties, the results indicated that all present some evidence of validity and reliability, but none report responsiveness. Implications: Given the impact that an instrument can have on analyzing the effects of an intervention, this study highlights the importance of considering not only the validity and reliability of an instrument but also responsiveness as a psychometric property, and the need to better describe the rationale for the outcome measures and specify what abilities are being targeted and measured. This will accurately guide future research and improve clinical decision-making around ASD.